2000
DOI: 10.1115/1.1326443
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Polyolester Under an EHD Contact in Some Refrigerant Environments

Abstract: EHD traction of polyol ester in some refrigerants is analyzed using the non-Newtonian theory, from which available rheological parameters are determined. Then the rheological parameters are studied in elation to refrigerant concentration. As a result, the viscosity pressure coefficient of the mixtures is inversely correlated with refrigerant concentration in terms of mole per volume, while the representative stress characterizing the non-Newtonian is positively correlated. When the viscous volume relating to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There was a decrease in viscosity reduction with an increase in the ratio of the HFC-134a solubility to the mean molecular weight of the lubricant. HFC-125, HFC-134a and HCFC-22 were used with POE lubricant by [59] to study the rheological properties of polyolester oil under elastohydrodynamic (EHD) contact conditions in refrigerant environments. Analytical work as well as experimentation involving a ball-on-disk EHD tester were used in this study.…”
Section: Hydrofluorocarbons (Hfcs)mentioning
confidence: 99%
See 1 more Smart Citation
“…There was a decrease in viscosity reduction with an increase in the ratio of the HFC-134a solubility to the mean molecular weight of the lubricant. HFC-125, HFC-134a and HCFC-22 were used with POE lubricant by [59] to study the rheological properties of polyolester oil under elastohydrodynamic (EHD) contact conditions in refrigerant environments. Analytical work as well as experimentation involving a ball-on-disk EHD tester were used in this study.…”
Section: Hydrofluorocarbons (Hfcs)mentioning
confidence: 99%
“…9 indicated that the relation of the viscous volume with the molecular volume can be represented by a single line irrespective of the refrigerants. [60] and the symbols are the measure data (a) at gas pressure of 100 kPa, (b) at gas pressure of 300 kPa [59].…”
Section: Hydrofluorocarbons (Hfcs)mentioning
confidence: 99%
“…However, as the EHD technique has shown an improvement of the heat transfer on refrigerant side (Muraki et al, 2001), it is believed that magnetic field could have an enhancement effect on heat transfer properties. Several studies have been reported on the use of magnetic elements in enhancing the performance in many applications such as oil, natural gas furnaces, diesel engines, fuel lines and also in water treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Muraki et al. 5 implemented a ball-on-disk elastohydrodynamic (EHD) test-rig within an autoclave for allowing a gas pressure environment. They measured film thickness and traction generated by mixtures of PE blended with HCFC-22, HFC-125, or HFC-134a: they further derived the averaged mixture rheological properties by fitting the experimental data with traction models.…”
Section: Background and Introductionmentioning
confidence: 99%